ANALISIS PENGARUH FAKTOR-FAKTOR FUNDAMENTAL RASIO KEUANGAN TERHADAP PERUBAHAN HARGA SAHAM - Daniarto Raharjo; Dul Muid (Diponegoro Journal of Accounting, 2013)
This research aims to analyze and check the influence of some fundamental factor of financial ratios that can be used to make prediction of the share price changes. The variables studied in this research were return on equity (ROE), return on asset (ROA), debt to equity ratio (DER), current ratio (CR), earning per share (EPS) and book value per share (BVS). This research used quantitative method by collecting secondary data from financial statement of non financial companies listed in LQ 45 index during the period 2007-2011 in Indonesia Stock Exchange (IDX). These data are tested with an analysis model using multiple linear regression. This analysis aims to determine the relation level of independent variables impact on dependent variable. The result of research indicated that fundamental variables represented on financial ratio ROE, ROA, DER, CR, EPS, and BVS simultaneously have significant effect on share price changes. Based on t-test result, separately showed only variable CR have significant effect on share price changes while other variables have no significant effect. The prediction ability from six variables to share price changes equal to 11,8% as shown by level of adjusted R Square 0,118 while the rest 88,2% influenced by other dissimilar factor which is not attempted into research model.